Experimental investigation of a dual-source powered absorption chiller based on gas engine waste heat and solar thermal energy. (August 2015) - Wang, Jialong; Wu, Jingyin; Wang, Hongbin
Abstract: A dual-source powered mixed effect AC (absorption chiller) is applied in a CCHP (combined cooling heating and power) system. This CCHP system integrates both fossil fuel energy and solar energy together. Refrigeration performance of this mixed effect AC under both waste heat mode and solar mode are tested and compared. In waste heat mode, the AC is simultaneously powered by exhaust gas waste heat and hot water waste heat from an ICE (internal combustion engine). And five working conditions under different electric output of ICE are tested to study the refrigeration performance. In solar mode, the AC is powered by hot water from a solar thermal collector matrix, and its refrigeration performance is tested in a selected day to study the operation characteristics. Test results show that, the mixed effect AC can reach a COP (coefficient of performance) of 0.91 in waste heat mode. But its COP is only about 0.6 in solar mode for there is only hot water heating source. Comparison results show that, waste heat mode is not necessarily better than solar mode and vice versa. In terms of primary energy consumption, waste heat mode is worse than solar mode when the part load ratio of ICE is below 0.62. Highlights: A dual-source powered mixed effect absorption chiller is applied in a CCHP system. This CCHP system integrates fossil fuel energy and solar energy together. Waste heat powered and solar thermal powered refrigeration are tested and discussed. The absorption chiller COP can reach 0.91 in waste heat mode and 0.6 in solar mode. Waste heat mode is better than solar mode when electric load is high, and vice versa.